Limited Utility of SIRS Criteria for Identifying Serious Infections in Febrile Young Infants - Osamu Nomura; Yoshihiko Morikawa; Takaaki Mori; Yusuke Hagiwara; Hiroshi Sakakibara; Yuho Horikoshi; Nobuaki Inoue (MDPI AG, 2021)
(1) Background: Young infants have a high risk of serious infection. The Systematic Inflammatory Response Syndrome (SIRS) criteria can be useful to identify both serious bacterial and viral infections. The aims of this study were to evaluate the diagnostic performance of the SIRS criteria for identifying serious infections in febrile young infants and to identify potential clinical predictors of such infections. (2) Methods: We conducted this prospective cohort study including febrile young infants (aged < 90 days) seen at the emergency department with a body temperature of 38.0 °C or higher. We calculated the diagnostic performance parameters and conducted the logistic regression analysis to identify the predictors of serious infection. (3) Results: Of 311 enrolled patients, 36.7% (n = 114) met the SIRS criteria and 28.6% (n = 89) had a serious infection. The sensitivity, specificity, positive predictive value, and positive likelihood ratio of the SIRS criteria for serious infection was 45.9%, 69.4%, 43.5%, 71.4%, 1.5, and 0.8, respectively. Logistic regression showed that male gender, body temperature ≥ 38.5 °C, heart rate ≥ 178 bpm, and age ≤ 50 days were significant predictors. (4) Conclusions: The performance of the SIRS criteria for predicting serious infections among febrile young infants was poor.